Design and evaluation of a novel nanoparticulate-based formulation encapsulating a HIP complex of lysozyme. (June 2013) - Gaudana, Ripal; Gokulgandhi, Mitan; Khurana, Varun; Kwatra, Deep; Mitra, Ashim K.
<x xml:space="preserve">Abstract</x> Formulation development of protein therapeutics using polymeric nanoparticles has found very little success in recent years. Major formulation challenges include rapid denaturation, susceptibility to lose bioactivity in presence of organic solvents and poor encapsulation in polymeric matrix. In the present study, we have prepared hydrophobic ion pairing (HIP) complex of lysozyme, a model protein, using dextran sulfate (DS) as a complexing polymer. We have optimized the process of formation and dissociation of HIP complex between lysozyme and DS. The effect of HIP complexation on enzymatic activity of lysozyme was also studied. Nanoparticles were prepared and characterized using spontaneous emulsion solvent diffusion method. Furthermore, we have also investigated release of lysozyme from nanoparticles along with its enzymatic activity. Results of this study indicate that nanoparticles can sustain the release of lysozyme without compromising its enzymatic activity. HIP complexation using a polymer may also be employed to formulate sustained release dosage forms of other macromolecules with enhanced encapsulation efficiency.